The experience of dry mouth and screening for Sjogren's syndrome by the dentist: patient-reported experiences - Boughanmi Rihab; El Houari Lina; Simon-Tillaux Noémie; Saide Jean; Gosset Marjolaine (BMC, 2023)
Abstract Background One of the main clinical features of Sjögren's Syndrome is oral dryness, which is associated with an increased risk of oral diseases and a lower oral life quality. Dentists have a key role to play in the Sjögren's Syndrome diagnosis and specific management. In parallel, many patients rely on patient associations, which offer opportunities for members to seek information about their disease and share their experiences. We aimed to evaluate patients experience with dry mouth and the importance of dentists in Sjögren's Syndrome diagnosis and its management. Methods We carried out a cross-sectional survey in 2020 based on a questionnaire drafted in collaboration with clinicians specializing in Sjögren's Syndrome and patient members of a patient association. The survey consisted of 27 questions divided into the six sections: the patient's profile, their experience with dry mouth and treatments used to manage, characteristics of experienced oral-health problems, effects of dry mouth and its consequences on the quality of life, evaluation of the dentist role in the screening of Sjögren's Syndrome, and its management by the dentist. Recruitment was carried out via the patient association's newsletter, website, and social networks. Sjögren's diagnosis was self-reported. Results One thousand four hundred fifty-eight patients fully responded to the survey. Most respondents were women over 50 and were mainly concerned with primary Sjögren's Syndrome. Overall, 86.97% of respondents reported experiencing frequent or constant dry mouth and 69.01% declared having had oral problems (candidiasis, oral pain, loss or alteration of taste, bad breath, gastro-esophageal reflux). We found a positive correlation between the frequency of dry mouth and each of these disorders and between the frequency of dry mouth and alterations in life quality dimensions. Finally, 74.9% of patients did not report having dry mouth to their dentist prior to being diagnosed with Sjögren's Syndrome and 58% had not been informed about the oral risks associated with it by their dentist and sought information themselves or from their physician. Conclusions We confirm the significant consequences of dry mouth on oral quality of life, as well as its association with oral health problems. Sjögren's Syndrome screening by dentists should be increased, as well as prevention of the associated oral health risks.